Audit of efficiency of the use of budgetary funds in the process of conducting a state audit - Shakirova, G.A.; Sitenko, D.A.; Vasa , L. (BUKETOV BUSINESS REVIEW, 2019)
In the article the audit of the effectiveness of the use of budgetary funds in the process of conducting a state audit on the example of ten adopted State programs in the Republic of Kazakhstan is discussed. Performance audit has a significant impact on the quality of execution and adoption by state executive bodies of decisions in the field of public financial management, and also contributes the increasement of responsibility, transparency and accountability of the activities of government bodies. The article provides an overview of the development of performance audit in different countries. The authors reviewed the wording of the performance audit in the world practice and the development of performance audit as an independent examination of the effectiveness and efficiency of the activities of state bodies. The problem of the audit of efficiency of state-owned enterprises is fundamentally new for Kazakhstani science and practice of public administration and is currently at the stage of scientific development. The authors paid attention to the disclosure of the main criteria and performance indicators during the performance audit. To determine the effectiveness of the execution of budget programs, criteria are used to evaluate current programs that ensure the current activities of state bodies and institutions, as well as quantitative and qualitative indicators characterizing the improvement of the performance of audited entities. In the article, the authors presented a detailed analysis of the performance audit of the implementation of state programs. The authors presented an assessment of existing state programs in respect of the allocated budgetary funds and established financial irregularities. The authors showed that performance audit took the appropriate place in the system of state and local financial control in the Republic of Kazakhstan.